(3VhA GdOgQs - (3eUWai (B((3Ch eMeO eUWai(B) (3Hf eMeO aGVd Hf eMeO Cejf GdTfbjWj Gdbdbej, CHh GdCfhGQ, GdedbH HeGA GdYjfjf, J (B1328 (3g` s
(3ChdgG (B:s
(3jbhd fLd aGVd fLd eGejf Ydeg edbH HeGA GdYjfjf s
(3BNQgG (B:s
(3Ke GdUdGI hGdSdGe SQeOkG Ydi GdfHi GdbQTi CMeOG heG LQi GdLfGf HGdGfgGQ hRNQa GdaQO hSQ HGdKeGA s
(3CQLhRIs
(3fSNI bOjeIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3ChQGbgG eJbUaI ef CWQGbgG s
(3GdfSNI HgG MhGT s
(3HgG fXGe GdJYbjHI s
Keywords: (3GdcjejGA h GdWHjYjGJs